Arms open wide a call to linger in the Saviors presence - Gragg, Sherri (Nashville, Tennessee Thomas Nelson, 2014)
The author writes in fictional narrative from while mixing biblical history with scripture, creating a setting that transforms readers back in time and places them right in Jesus presence for thirty-four days readers walk with the Savior to witness miraculous healings and events, and give fresh insight into his power by thinking and feeling with people whose lives became instantly transformed by his love and grace.
Keywords: Devotional literature; Christian life -- Devotional literature; Jesus Christ -- Devotional literature